STRESS: WHAT WE ACTUALLY KNOW ABOUT THIS RISK FACTOR? - R. G. Oganov; G. V. Pogosova (Столичная издательская компания, 2015)
Results of current studies devoted to relationship between stress and cardiovascular morbidity and mortality were analyzed. The types of stressful reactions are presented: acute and chronic stress as well as models of working stress. Pathophysiological modes of interactions of stress and cardiovascular diseases are presented. Effective methods of stress correction are described. Clinical and prognostic importance of therapy approaches is discussed.